2004
DOI: 10.2320/matertrans.45.689
|View full text |Cite
|
Sign up to set email alerts
|

Low Cycle Fatigue Properties of Ni added Low Silver Content Sn-Ag-Cu Flip Chip Interconnects

Abstract: The straddle fatigue test has been performed to study the fatigue properties of Sn-1.2 mass%Ag-0.5 mass%Cu-0.05 mass%Ni for flip chip interconnections. The low cycle fatigue resistance of the alloy is equivalent to that of Sn-3 mass%Ag-0.5 mass%Cu alloy, even though the fatigue endurance of Sn-1 mass%Ag-0.5 mass%Cu alloy was poorer than that of the 3 mass%Ag alloy. The alloy has fine microstructure and Ag 3 Sn intermetallic compound makes a network structure together with fine (Cu,Ni) 6 Sn 5 compound. The micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Recently, thermal 7) and isothermal fatigue properties 8) of Sn-1.2Ag-0.5Cu solder joints are improved by a small amount of nickel addition (0.05 mass%Ni) into the solder, and thermal fatigue life of Sn-1.2Ag-0.5Cu-0.05Ni solder joint is shown as long as that of Sn-3Ag-0.5Cu. 7) These properties strongly correlate to microstructure of the solder, and good thermal fatigue properties of Sn-1.2Ag-0.5Cu-0.05Ni are due to both fine Sn grains in an initial solder joints and suppression of Sn-grain-coarsening after thermal fatigue test.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, thermal 7) and isothermal fatigue properties 8) of Sn-1.2Ag-0.5Cu solder joints are improved by a small amount of nickel addition (0.05 mass%Ni) into the solder, and thermal fatigue life of Sn-1.2Ag-0.5Cu-0.05Ni solder joint is shown as long as that of Sn-3Ag-0.5Cu. 7) These properties strongly correlate to microstructure of the solder, and good thermal fatigue properties of Sn-1.2Ag-0.5Cu-0.05Ni are due to both fine Sn grains in an initial solder joints and suppression of Sn-grain-coarsening after thermal fatigue test.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Among lead-free solders, ternary Sn-Ag-Cu solders [3][4][5][6][7][8][9][10][11] are expected to be the substitute of a Sn-Pb eutectic solder, and have become wide spread in the manufacture of many electronic devices. However, the advanced lead-free solder, which has higher reliability than ternary Sn-Ag-Cu solders, is required to be used for various industry machines.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows a comparison of the tensile fracture subsurface of specimens with varying Ni content, and the fracture characteristics show that the -Sn phase possessed a tensile plastic deformation flow after tensile testing, thus the -Sn phase was the main deformation mechanism. According to relevant reports [8][9][10][11][12][13][14][15][16] and comparing Fig. 3 with Fig.…”
Section: Observation Direction Of the Fracture Subsurfacementioning
confidence: 99%
“…[1][2][3] Under drop tests and pull tests, many reports have shown that the fracture resistance of Sn based solders can be enhanced by a very small addition of Ni, RE etc. [4][5][6][7][8] Also, related studies 4,5,[9][10][11][12][13] have revealed that Ni addition (>3000 ppm) has a significant influence on the microstructure, creep, shear strength, fatigue properties and the characteristics of intermetallic compounds (IMC) in the interface. However, the studies emphasized the interfacial effect between solders and substrate; the relationship between the bulk solder and microsegregation has not been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation